Perceptions of heart failure symptoms, disease severity, treatment decision-making and side effects by patients and cardiologists: a multinational survey in a cardiology setting - Bruce Wirta S; Balas B; Proenca CC; Bailey H; Phillips Z; Jackson J; Cotton S (Dove Medical Press, 2018)
Sara Bruce Wirta,1 Bogdan Balas,2 Catia C Proenca,3 Hollie Bailey,4 Zoe Phillips,4 James Jackson,4 Sarah Cotton4 1Real World Evidence, Cardio-Metabolic Franchise, Novartis Sweden, Stockholm, Sweden; 2Real World Evidence, Cardio-Metabolic Franchise, Novartis Pharma, Basel, Switzerland; 3Wellmera AG, Basel, Switzerland; 4Real World Research, Adelphi Real World, Bollington, UK Purpose: Explore the extent to which heart failure (HF) symptoms and side effects of HF treatment experienced by patients are recognized by cardiologists, and concordance between patient–cardiologist perceptions of HF severity and patients’ contributions to treatment decision-making. Methods: A multinational, cross-sectional survey of cardiologists and patients with HF was conducted. Patient-record forms (PRFs) were completed by cardiologists for consecutive consulting patients with HF, who completed a patient self-completion questionnaire (PSC). Responses from PRFs with an associated PSC were analyzed to compare patient- and cardiologist-reported occurrences of HF symptoms and treatment side effects, patient-perceived severity of HF and cardiologists’ perceived risk of death within 12 months, and patient input into treatment decisions. Concordance was calculated as the number of response agreements between PSCs and PRFs for total number of matched pairs. Over- or underreporting of symptoms and side effects by cardiologists relative to patient-reported occurrences were calculated. Results: Overall, 2,454 patient–cardiologist pairs were identified. High levels of concordance between matched pairs were observed for the occurrence of reported HF symptoms (93%), side effects (77%–98%) and degree of patient input into treatment decisions (74%); for perceived HF severity, concordance was 54%. Most symptoms (except dyspnea when active and fatigue/weakness, experienced by >50% of patients) were underreported by cardiologists. Of patients reporting to have been informed by their cardiologist that their HF was mild, 28% were perceived by their cardiologist to have a moderate–high/very high risk of death within 12 months. Treatment choice was not discussed with almost a third of patients. When discussed, 94% of patients (n=1,540) reported the cardiologist made the final decision. Cardiologists more often under- than overreported the occurrence of side effects reported by patients. Conclusion: Improved patient–cardiologist dialogue and shared decision-making is required for optimizing patient care and outcomes in HF. Keywords: patient influence, disease awareness, treatment decision-making, patient-reported outcomes, disease-specific program, real world